CONOTATIVE AND DENOTATIVE MEANINGS IN THE LYRICS OF THE BTS SONG “PERMISSION TO DANCE” (SEMANTIC ANALYSIS) (Karya Ilmiah Mahasiswa (KIMA), 2022)
Literature is the result of human work which covers all of life which is conveyed through language. Semantics is a branch of study in linguistics. In general linguistics, semantic analysis refers to the analysis of the meaning of words, fixed expressions, complete sentences, and utterances in context. The purpose of this analysis is to find out some words that contain connotative and denotative meanings. Both denotative and connotative meanings have a relationship based on the word and the world. The lyrics of the song "Permission to Dance" by BTS (Bangtan Sonyaendan) were analyzed using a qualitative descriptive approach in finding denotative and connotative meanings. COVID-19.